2020
DOI: 10.1186/s12931-020-01568-w
|View full text |Cite
|
Sign up to set email alerts
|

ROBO2 signaling in lung development regulates SOX2/SOX9 balance, branching morphogenesis and is dysregulated in nitrofen-induced congenital diaphragmatic hernia

Abstract: Background Characterized by abnormal lung growth or maturation, congenital diaphragmatic hernia (CDH) affects 1:3000 live births. Cellular studies report proximal (SOX2+) and distal (SOX9+) progenitor cells as key modulators of branching morphogenesis and epithelial differentiation, whereas transcriptome studies demonstrate ROBO/SLIT as potential therapeutic targets for diaphragm defect repair in CDH. In this study, we tested the hypothesis that (a) experimental-CDH could changes the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
(67 reference statements)
2
12
0
Order By: Relevance
“…As we had previously demonstrated in fetal lung explants harvested at the pseudoglandular stage [7], AFSC-EVs administered to explants harvested at both canalicular and saccular stages rescued the expression of both FGF10 and FGFR2 back to control levels. The ROBO/SLIT pathway is also essential for normal lung development, as shown in knock-out studies [34,35], and is downregulated in nitrofen-exposed lungs of fetuses with CDH [36]. In the present study, we confirmed the upregulation of ROBO1 and the corresponding downregulation of ROBO2 and SLIT2 expression in nitrofen-exposed lungs at both timepoints, which were rescued by AFSC-EV treatment to control levels.…”
Section: Discussionsupporting
confidence: 87%
“…As we had previously demonstrated in fetal lung explants harvested at the pseudoglandular stage [7], AFSC-EVs administered to explants harvested at both canalicular and saccular stages rescued the expression of both FGF10 and FGFR2 back to control levels. The ROBO/SLIT pathway is also essential for normal lung development, as shown in knock-out studies [34,35], and is downregulated in nitrofen-exposed lungs of fetuses with CDH [36]. In the present study, we confirmed the upregulation of ROBO1 and the corresponding downregulation of ROBO2 and SLIT2 expression in nitrofen-exposed lungs at both timepoints, which were rescued by AFSC-EV treatment to control levels.…”
Section: Discussionsupporting
confidence: 87%
“…The ROBO/SLIT pathway is also essential for normal lung development, as shown in knockout studies, 36 , 37 and is downregulated in nitrofen-exposed lungs of fetuses with CDH. 38 In the present study, we confirmed the upregulation of ROBO1 and the corresponding downregulation of ROBO2 and SLIT2 expression in nitrofen-exposed lungs at both time points, which were rescued by AFSC-EV treatment to control levels. When we assessed factors involved in sending guidance cues for lung branching, we confirmed that the Ephrin pathway was downregulated at the saccular stage, as previously reported, 39 and rescued by AFSC-EV treatment to control levels.…”
Section: Discussionsupporting
confidence: 84%
“…ROBO2 has been found to regulate different physiological functions and tumor development. Gonçalves et al [18] revealed an important role of ROBO2 in lung development. Escot et al [19] found that ROBO2 plays an important role in pancreas cell identity and plasticity.…”
Section: Discussionmentioning
confidence: 99%